Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays saccharata Sturt) Varietas Bonanza F1 yang Diaplikasikan Beberapa Konsentrasi Biosaka - Sainuddin; Muhanniah; Fenny Hasanuddin (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2025)
Sweet corn is commonly known as sweet corn is one of the horticultural commodities that has a high carbohydrate source. Biosaka is an elicitor in the form of a material made from a solution of plants or grasses that can protect plants from diseases and pests and reduce the use of chemical fertilizers by 50-90%. The use of Biosaka for farmers can support the development of organic farming. This study aims to determine the effect of several Biosaka concentrations on the growth and production of sweet corn (Zea mays saccharata Sturt) Bonanza F1 variety and determine the best concentration. The study was conducted in Rappang Village, Panca Rijang District, Sidenreng Rappang Regency, South Sulawesi, from February to June 2025. The study used a one-factor Randomized Block Design (RAK), namely Biosaka concentration with five levels (0 ml, 25 ml, 50 ml, 75 ml, and 100 ml/15 liters of water) with three replications. The parameters observed included plant height, number of leaves, flowering age, number of seeds per row, number of rows per cob, and production per unit. The results showed that the provision of Biosaka did not have a significant effect on all parameters, but a concentration of 75 ml/15 L gave the highest results for most parameters.